Using System Dynamics Simulation to Understand the Feedback Process in a Construction Project - Zainab, A. Malik; Cheng, Jack Kie (ESB Business School, 2016)
The fast changing, complex, and dynamic environment in the construction project nowadays has led to frequent occurrences of last minute changes and reworks. Such frequent occurrences can influence performance in terms of project completion time, which the completion time will result in delay and have an impact on the quality of the project. Usually, reworks occur because of last minute changes in order to fulfill the client’s request or because of a decision made by the project manager. The Project Management Institute (PMI) has introduced the Project Management Body of Knowledge (PMBOK) as a standard guide that explains the different knowledge areas involved and needed to be taken into account when managing a project. As managing a construction project is complex and complicated, in addition to the project manager’s lack of understanding on how different knowledge areas may influence other knowledge areas, the problem of project delay due to rework become inevitable. Therefore, the aim of this paper is to identify the interconnectivity and interrelationship between different knowledge areas in PMBOK using the System Dynamics (SD) simulation model. A construction project model of simulation was developed using Causal Loop Diagrams (CLD) as well as Stock and Flow Diagram (SFD). With the model, it is anticipated the project manager will be able to understand the feedback process of the project in order to prevent delays. The development of simulation model can be used to help and support the project manager in the process of planning and managing the construction project efficiently and making timely effective decision-making.